1976
DOI: 10.1111/j.1365-2125.1976.tb00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification by diazepam or thioridazine of the psychomotor skills related to driving: a subacute trial in neurotic out‐patients.

Abstract: 1Forty-five out-patients with clinically manifested anxiety were tested in order to study the effects of 2 weeks' treatment with placebo, diazepam (5-10 mg three times daily) or thioridazine (25-50 mg three times daily) on their psychomotor skills related to driving. 2 When compared with placebo, diazepam increased the number of mistakes in reaction and co-ordination tests and also decreased.ability to discriminate the fusion of flickering light.3 When compared to other groups, reactive and co-ordinative skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0
1

Year Published

1979
1979
1991
1991

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…The effects were similar to those obtained in healthy vol unteers . Similar results were also obtained by Linnoila and his group who, in two studies, found that diazepam in the same dose we used, impaired tracking and divided attention task performance in pa tients and volunteers alike [Saario et al, 1976;Linnoila et al. 1983], These results are reassuring to investigators in the field of behavioral effects of benzodiazepines as they confirm that results obtained in healthy volunteers can be applied to anxious patients.…”
Section: Discussionsupporting
confidence: 79%
“…The effects were similar to those obtained in healthy vol unteers . Similar results were also obtained by Linnoila and his group who, in two studies, found that diazepam in the same dose we used, impaired tracking and divided attention task performance in pa tients and volunteers alike [Saario et al, 1976;Linnoila et al. 1983], These results are reassuring to investigators in the field of behavioral effects of benzodiazepines as they confirm that results obtained in healthy volunteers can be applied to anxious patients.…”
Section: Discussionsupporting
confidence: 79%
“…However, the results obtained in healthy volunteers have previously been applicable to subacute (2 weeks) treatments of outpatients with anxiety (Saario et al 1976) and depression (Sepp~il/i et al 1978). Saario et al (1976) documented an impairment of psychomotor functions both with diazepam (15-30 mg daily) and with thioridazine (75-150 mg daily).…”
Section: Discussionmentioning
confidence: 99%
“…Even 2 weeks' treatment with diazepam had no anxiolytic effects in terms of the patient-rated Morbid Anxiety Inventory (Bonn, Salkind & Linford Rees, 1971) and most studies could not detect anxiolytic effects in terms of psychiatrists' ratings after 1 week of treatment for example with nitrazepam (Malpas et al, 1974) and nordiazepam (Tansella et al, 1974). Definite clinical effects as evaluated by psychiatrists were found only after 2 weeks of treatment with clorazepate (Robin, Curry & Whelpton, 1974) and diazepam (Saario, Linnoila & Mattila, 1976;Dasberg, 1975). Because of the experimental design chosen for this study, and the high drop-out rate, a prolongation of each treatment for another week, requiring the patients to stay 2 months in hospital was impracticable.…”
Section: Discussionmentioning
confidence: 99%